Application of the boundary-element method to the interaction of light with single and coupled metallic nanoparticles - Rockstuhl, Carsten; Salt, Martin Guy; Herzig, Hans-Peter (My University, 2003)
The boundary-element method is applied to the interaction of light with resonant metallic nanoparticles. At a certain wavelength, excitation of a surface plasmon takes place, which leads to a resonantly enhanced near-field amplitude and a large scattering cross section. The resonance wavelength for different scatterer geometries is determined. Alteration of the scattering properties in the presence of other metallic nanoparticles is discussed. To treat this problem, a novel formulation of the boundary-element method is presented that solves the interaction problem for all the coupled particles.
Keywords: diffraction theory; surface plasmons